035 The TOS study: can we use our patients to help improve the quality of neurological referral?. Issue 3 (9th February 2012) - Yap, C; Appleton, J; Crossley, D; Nicholl, D J
Abstract : Background: We have previously shown that providing more ophthalmoscopes and training does not necessarily increase Foundation Years level of confidence at using an ophthalmoscope. Thus we developed a simple scoring system as an indirect measure of the quality of neurological examination skills- the TOS score, ie asking the patient if they could recollect being examined with a Tendon hammer (T), Ophthalmoscope (O) and Stethoscope (S)- the latter as a measure of recall. Methods: We assessed TOS scores in 59 in-patients referred for a neurological opinion in two NHS Trusts. Results: In Trust A (n=29)—27% of patients could not recall being examined with an ophthalmoscope, 11% could not recall being examined with a tendon hammer. In Trust B (n=30)—80% of patients could not recall ophthalmoscopy, 50% could not recall being examined with a tendon hammer. In both Trusts, only 3% of patients could not recall being examined with a stethosope. Conclusions: Measurement of TOS scores on patients referred to neurology is a simple method of measurement of quality of in-patient neurological assessment. The results can be feedback to the referring team- we have provided feedback on TOS scores to all medical staff as part of an ongoing survey. Of greater concern, the TOS scores can show how 'Neurology NAD' in the notes may actually mean 'Neurology not actually done' which has important implications.